Efektivitas Board Game Codenames terhadap Peningkatan Fungsi Kognitif dan Interaksi Sosial Pasien - Ganut, Felisima; Rahayu, Fransiska Anita; Amoly, Daniela (Universitas Hang Tuah Pekanbaru, 2025)
Cognitive impairment and difficulties in social interaction are frequent challenges among post-stroke patients, often hindering the rehabilitation process. The board game Codenames, which incorporates word-association strategies and team-based cooperation, offers a simple intervention to stimulate cognitive abilities while fostering social engagement. This study investigated the effectiveness of Codenames in improving cognitive function and social interaction among post-stroke patients. A quasi-experimental design with a pre-test–post-test control group was employed, involving 50 participants divided into an intervention group (n = 25) and a control group (n = 25). Cognitive function was assessed using the Montreal Cognitive Assessment–Indonesia (MoCA-Ina), while social interaction was measured with the RAND Social Health Battery (RSHB). Data were collected between July and August 2025 at the Stroke Center of Dadi Regional Special Hospital, Makassar. Statistical analyses were conducted using the Wilcoxon Signed Rank Test and the Mann–Whitney U Test. Results demonstrated significant improvement in cognitive function within the intervention group (p < 0.001), whereas no significant change was observed in the control group (p = 0.972). Social interaction also improved significantly in the intervention group (p < 0.001), though no significant difference was found between groups (p = 0.853). These findings suggest that Codenames may serve as an effective complementary therapy for cognitive stimulation and has potential to support social interaction when consistently implemented with family involvement.